PELP1: A novel therapeutic target for hormonal cancers - Chakravarty, Dimple (2010)
Recent studies implicate the estrogen receptor (ER) coregulator proline-, glutamic acid-, and leucine-rich protein (PELP) 1 as playing critical roles in ER-genomic, ER-nongenomic and ER-signaling cross talk with growth factor signaling pathways. PELP1 expression is deregulated in hormonal cancers and recent studies further elucidated the molecular mechanisms by which PELP1 regulates hormone therapy response. Although PELP1 is important for normal functions of the ER, the possibility to target ER-PELP1 axis appears to be an effective strategy for preventing hormonal carcinogenesis and therapy resistance. Thus, PELP1 may be useful as prognostic marker for hormonal cancers and PELP1 signaling may be useful to generate targeted therapeutics to overcome hormonal therapy resistance.